Employment of Graduates of Pedagogical Universities: Statistics vs Mythology - L. M. Nurieva; S. G. Kiselev (Образование и наука)
Introduction. Today, one of the most debatable issues currently discussed in the professional community is the problem of the effectiveness of teacher education system. A significant number of the leaders of the educational sector and the expert community are convinced that teacher training system has long ceased to meet the challenges of the time and needs to be reorganised. The most radical position was declared at the Higher School of Economics: “To stop the degradation of education, it is necessary to include all pedagogical institutions of higher education into the composition of classical universities, as it is done in most Anglo-Saxon countries”. The underlying claims to the pedagogical system are the significant extent to which graduates of pedagogical institutions avoid working in their specialty, as well as the overproduction of pedagogical specialists in the absence of need for them. Meanwhile, instead of substantiated quantitative estimates of these phenomena in the literature, we will find only approximate figures calculated on limited statistics obtained by experts. The aim of the present research is to review the results of employment of graduates of higher education institutions trained in teacher specialties, relying on a new information base – federal statistical observation form No. ОО-1 “Information about the organisation providing training for educational programmes of primary general, basic general, secondary general education”, and the assessment of the effectiveness of teacher education system based on a quantitative approach. Methodology and research methods. The methodological framework of the research is based on the systematic approach in which general scientific (comparative, retrospective analysis, systematization, generalisation) and statistical research methods (statistical and correlation analysis, etc.) were employed. Results and scientific novelty. In the current research, it is proved that the allegations of low efficiency of the system of teacher education are untenable. In assessing the profile employment of graduates, the market for pedagogical labour is limited by experts to job vacancies in secondary schools, while institutions of pre-school, additional, special correctional, as well as secondary and higher professional education fall out of sight. Moreover, graduates of all pedagogical specialties (educators, masters of vocational training, speech therapists, psychologists, additional education teachers, etc.), as well as extramural graduates, are mistakenly included in the number of young specialists – teachers. As a result, the actual amount of teacher training is unjustifiably overstated. A comparison of overstated training with an understated number of jobs inevitably leads to erroneous estimates of the effectiveness of the training system. In addition, it was established that the admission to schools of young teachers of higher qualification is 25–30% higher than the actual graduation of students of teaching specialties of the full-time department of universities, which would be impossible if the graduate employment profile was low. This excess is explained by the minimisation of the volume of teacher training to a critical level and the growing recruitment to teacher positions of non-specialists teachers, which is caused by errors in planning of determining the benchmarks for enrollment to study at universities. Practical significance. The authors believe that this article will allow to clarify approaches to assessing the effectiveness of teacher education system and adjust the control figures for university admission in the field of “Education and Pedagogical Sciences” in accordance with the current personnel supply and demand.